VD_FINDINFO Jug / 2017 / 94 vom 31. Oktober 2016 - VD Tribunal cantonal (2016)
RIXE, PRÉSOMPTION D'INNOCENCE, ATTÉNUATION DE LA PEINE, FIXATION DE LA PEINE | 133 CP, 47 CP, 48 let. e CP, 10 al. 3 CPP (CH)